Investigating the incorporation of precision teaching assessment methods within a structured approach for children with autism - Beeson, Paul (2013)
The aim of this research was to investigate the incorporation of a 'structured approach' to teaching children with autism, with precision teaching assessment methods. The rationale for the research focused on the limited evidence base regarding educational approaches for children with autism (Jones, 2002), and the growing need to provide appropriate educational provision for this group (Ali & Frederickson, 2006). One of the more widely used approaches in the UK is 'Treatment and Education of Autistic and related Communication handicapped Children' (TEACCH) (Tutt, Powell, & Thornton, 2006), with a derivative of this, called a 'structured approach', in place in the local context of the research.